The buying behaviour from a consumer perspective on green product - Lim, Xiao Xuan (2024)
This study aims to investigate the factors affecting consumers’ green product buying behaviour in Malaysia. Consumer consumption as the source of diverse socioeconomic effects is giving rise to a new paradigm shift in consumer behaviour towards green product purchases. Although some studies have examined the consumers’ purchase behaviour in the green context but a study that incorporates the Theory of Consumption Values (TCV) is rarely found in Malaysia. Based on this consideration, the TCV is applied as the guiding theory in this research. Conditional value, emotional value, attitude and environmental consciousness are included in the research framework to evaluate their influence on consumers’ green product purchase behaviour. With that, questionnaires are distributed to 200 adult Malaysian consumers by applying convenience sampling. The collected data are then analyzed using Pearson’s Correlation Analysis and Multiple Regression Analysis. Results indicate that conditional value, emotional value and environmental consciousness have a significant positive effect on consumers’ green purchase behaviour while attitude has no relationship with the dependent variable. Lastly, the theoretical and managerial implications of these findings are discussed, and several recommendations are proposed to future researchers.